Scientific Literacy Ability Through Speed Reading Methods in Class V Elementary School Students - Yeni Sulaeman; Ade Hikmat; Imam Safii; Aan Aan; Muhardila Fauziah; Usep Saepul Mustakim; Ajeng Muliasari; Dine Trio Ratnasari (Jurnal Penelitian Pendidikan IPA, 2023)
The teacher has not provided a special method to improve reading skills, the teacher has not measured the students' reading speed and the percentage of understanding of the reading content that the students have achieved, apart from that, the students also think that reading is a very boring lesson Reading is an important skill that can have implications for other literacy skills. However, the average reading ability of SDN 1 Nameng students is still not optimal. The aim of this research is to improve students' reading literacy skills by using the speed reading method on students' science lesson material. The method used in this research is action research which refers to the Kemmis and Mc Taggart model using a spiral system cycle consisting of planning, implementing actions, observation and reflection. The results of class actions in cycle I averaged 72.34% and increased in cycle II with an average of 80.46%. The conclusion of the class action carried out shows that the speed reading method is able to improve students' reading literacy skills in science subject matter